The Wesleyan Enlightenment: Closing the gap between heart religion and reason in Eighteenth Century England - Holgerson, Timothy Wayne (Kansas State University, 2017)
John Wesley (1703-1791) was an Anglican priest who became the leader of Wesleyan Methodism, a renewal movement within the Church of England that began in the late 1730s. Although Wesley was not isolated from his enlightened age, historians of the Enlightenment and theologians of John Wesley have only recently begun to consider Wesley in the historical context of the Enlightenment. Therefore, the purpose of this study is to provide a comprehensive understanding of the complex relationship between a man, John Wesley, and an intellectual movement, the Enlightenment. As a comparative history, this study will analyze the juxtaposition of two historiographies, Wesley studies and Enlightenment studies. Surprisingly, Wesley scholars did not study John Wesley as an important theologian until the mid-1960s. Moreover, because social historians in the 1970s began to explore the unique ways people experienced the Enlightenment in different local, regional and national contexts, the plausibility of an English Enlightenment emerged for the first time in the early 1980s. As a result, in the late 1980s, scholars began to integrate the study of John Wesley and the Enlightenment. In other words, historians and theologians began to consider Wesley as a serious thinker in the context of an English Enlightenment that was not hostile to Christianity. From a review of the historical literature, this dissertation details six links that scholars have introduced in their study of Wesley’s relation to the Enlightenment. However, the review also reveals two problems, one obstacle and one omission, that hinder new innovation and further study. Therefore, as a solution, this study introduces five lenses adapted from the recent scholarship of four historians and one historical theologian that provide new vantage points for considering the enlightenment of Wesley and Wesleyan Methodists, which together form the Wesleyan Enlightenment. Finally, based on the evidence gathered by using these new lenses, this study argues that because Wesley not only engaged the Enlightenment, but also addressed the spiritual needs and practical concerns of Wesleyan Methodists for more than fifty years in what he referred to as an enlightened age, John Wesley was a central figure in the eighteenth-century English Enlightenment.
Keywords: Wesleyan Enlightenment; John Wesley; English Enlightenment; Enlightenment studies; Wesley studies; Spiritual direction